Analisis Potensi Perikanan Tangkap di Kabupaten Ngada dalam Meningkatkan Kesejahteraan Masyarakat - Beko, Maria Faustina; Sagajoka, Estherlina; Luciany, Yohanes Paulus (Program Studi Ekonomi Pembangunan Universitas Flores, 2022)
This study aims to find out how the potential for capture fisheries in Ngada Regency. This research uses quantitative research methods. Data collection through written information about an object, subject or event in the form of archives or documents at the Ngada District Fisheries Service. With the Shift Share analysis technique which is a technique for analyzing changes in the structure of the regional economy with the national (Provincial) economy. The results of this study indicate that the capture fisheries potential in Ngada Regency in 2016-2022 which is calculated using Shift Share analysis, shows: the National Share component, the regional capture fisheries potential of Ngada Regency is positive; the Proportional Shift component, the shift in regional economic growth in Ngada Regency to the economy at the NTT Province level is positive; and the Differential Shift component, the economy of Ngada Regency to the economy at the NTT Province level is negative, meaning that all capture fisheries potential in Ngada Regency has poor competitiveness with other regions/districts in NTT Province.